War, Peace, and Human Nature 2013
DOI: 10.1093/acprof:oso/9780199858996.003.0018
|View full text |Cite
|
Sign up to set email alerts
|

Chimpanzees, Warfare, and the Invention of Peace

Abstract: This chapter reviews the evidence for warlike behavior in chimpanzees and discusses what these findings can tell us about human warfare. It begins with a review of the behavioral ecology of aggression, continues with an overview of the behavioral ecology of intergroup aggression in chimpanzees, and concludes with discussion of the implications for understanding the origins of war and prospects for peace in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(19 citation statements)
references
References 113 publications
(213 reference statements)
0
19
0
Order By: Relevance
“…Encounters with neighbours (‘intergroup encounters’ hereafter) occur most often in boundary areas (Wilson et al 2012) and may include lethal aggression, which can account for a substantial proportion of total mortality (e.g. 9.3% at Gombe, 3.8% at Mahale Mountains National Park, Tanzania; Wilson 2013). Similar to hunting red colobus monkeys, the outcome of an intergroup encounter depends on the number of participants; parties with more males are more likely to call in response to vocalizations from simulated (Wilson et al 2001) and real (Wilson et al 2012) intruders.…”
mentioning
confidence: 99%
“…Encounters with neighbours (‘intergroup encounters’ hereafter) occur most often in boundary areas (Wilson et al 2012) and may include lethal aggression, which can account for a substantial proportion of total mortality (e.g. 9.3% at Gombe, 3.8% at Mahale Mountains National Park, Tanzania; Wilson 2013). Similar to hunting red colobus monkeys, the outcome of an intergroup encounter depends on the number of participants; parties with more males are more likely to call in response to vocalizations from simulated (Wilson et al 2001) and real (Wilson et al 2012) intruders.…”
mentioning
confidence: 99%
“…If the attacks on neighboring communities lead to their extinction, as can happen (Goodall, ; Wilson, ), or is suspected (Nishida et al, ) the latter's females may eventually join the attacking community (Williams et al, ; Emery Thompson et al, ; Wilson, ). In that case, the higher‐ranking males may still show reduced tolerance toward these females, but are in due course forced to accept the new status quo.…”
Section: Discussionmentioning
confidence: 99%
“…Chimpanzees engage in lethal raiding, in which a party of patrolling males occasionally invades a territory and together attack and sometimes kill vulnerable members of neighboring communities (Wrangham,1999). However, attackers do not merely target the adult males of the neighboring community, but also their infants, juveniles and adult females (Goodall, ; Wrangham, ; Watts and Mitani, ; Watts et al, ; Williams et al, ; Wilson, ) of the neighboring community. Even though females with sexual swellings tend to receive less aggression (Wolf and Schulman ; Williams et al, ; Wilson, ), the fact remains that females that are not sexually attractive can be the target of serious male aggression.…”
mentioning
confidence: 99%
“…This is also true of our closest cousins, the chimpanzees, among which intragroup killing, as well as in intergroup fighting and killing to the point of group extermination have been documented . Recent studies of several communities of chimpanzees have found their violent mortality rates to be: in one community, 20% generally, 24% among males; in another one 36% (generally); and in a third one 16% (generally). Another comprehensive study of six chimpanzee populations has set the median number of violent deaths among them at 271 per 100,000 individuals per year, as compared with 164 per 100,000 per year, which the authors calculated as the average among human hunter‐gatherers .…”
Section: Classical Rousseauism and Extended Rousseauism: Their Rise Amentioning
confidence: 92%